1988
DOI: 10.1002/mrc.1260260402
|View full text |Cite
|
Sign up to set email alerts
|

Variable‐temperature NMR studies of thyroid hormone conformations

Abstract: 'H NMR spectra at 300 and 400 MHz have been recorded for the thyroid hormones thyroxine (T4) and triiodothyronine (T3) over a range of temperatures from 175 to 298 K in MeOH-d, . Above 200 K the aromatic region of the NMR spectrum of T4 consists of two peaks, one for the H-2',H-6' protons and one for H-2,H-6. As the temperature is lowered each of these resonances first broadens and then splits into two peaks of equal intensity at low temperature. This is consistent with dowed exchange between two equally popul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

1994
1994
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 10 publications
0
11
0
Order By: Relevance
“…The conformational flexibility and internal dynamics in thyroid hormones in solution have been studied earlier by NMR spectroscopy. Similar to the three-dimensional structures of thyroid hormones observed in the X-ray structures, these studies also indicated the roughly perpendicular arrangement of the two iodinated rings and the rapid movement of the phenolic ring about the diphenyl ether linkage. As discussed earlier, rotation of the phenolic ring about the O3–C1′ bond in T3 gives rise to the formation of proximal and distal conformers.…”
Section: Resultsmentioning
confidence: 52%
“…The conformational flexibility and internal dynamics in thyroid hormones in solution have been studied earlier by NMR spectroscopy. Similar to the three-dimensional structures of thyroid hormones observed in the X-ray structures, these studies also indicated the roughly perpendicular arrangement of the two iodinated rings and the rapid movement of the phenolic ring about the diphenyl ether linkage. As discussed earlier, rotation of the phenolic ring about the O3–C1′ bond in T3 gives rise to the formation of proximal and distal conformers.…”
Section: Resultsmentioning
confidence: 52%
“…When a series of variable temperature spectra was recorded to measure the energy barrier for rotation about the ether linkage of T4 and T3, an unexpected separation of the inner ring H2,6 resonance was observed, in addition to the expected separation of the H2‘,6‘ resonance that had been reported earlier in some thyroid hormone analogues . The origin of this phenomenon was not identified, but it suggests the presence of more complicated internal motions than simple rotation of the outer ring.…”
Section: Introductionmentioning
confidence: 79%
“…Previous variable temperature studies at 300 and 400 MHz have shown that the H2′,6′ resonance of thyroxine observed at room temperature is an averaged signal resulting from the rapid exchange of proximal and distal environments and that the two protons yield separate signals at low temperature. 8 The focus in the previous study was on the barrier to rotation of the outer ring, which was determined from a line shape analysis of the coalescing H2′ and H6′ resonances, but at temperatures just above the freezing point of methanol, partial separation of the H2,6 inner ring resonances was also reported. The separation of a resonance due to ortho protons in a substituted benzene derivative is somewhat unusual and is further investigated in the current study.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations